2001
DOI: 10.1128/mcb.21.20.6927-6938.2001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Impaired Muscle Differentiation in Myotonic Dystrophy

Abstract: Differentiation of skeletal muscle is affected in myotonic dystrophy (DM) patients. Analysis of cultured myoblasts from DM patients shows that DM myoblasts lose the capability to withdraw from the cell cycle during differentiation. Our data demonstrate that the expression and activity of the proteins responsible for cell cycle withdrawal are altered in DM muscle cells. Skeletal muscle cells from DM patients fail to induce cytoplasmic levels of a CUG RNA binding protein, CUGBP1, while normal differentiated cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
196
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(209 citation statements)
references
References 42 publications
10
196
0
3
Order By: Relevance
“…The strong reduction of the mutated DMPK transcripts by the (CUG)13 antisense could explain the restored differentiation of the infected DM1 myoblasts. This possibility is also supported by the recent report of Timchenko et al 33 showing that alterations in the activity of the CUGBP1 by the mutant DMPK transcripts causes disruption of p21-dependent control of cell cycle arrest, rendering DM1 myoblasts incapable of withdrawing from the cell cycle and fuse to form myotubes. We demonstrated that the misregulation of the CUG-binding protein in DM1 myoblasts was corrected in the antisense-infected DM1 myoblasts, indicating that molecular alterations induced by the mutated DMPK transcript were reversed by the expression of the (CUG) 13 antisense in DM1 cells.…”
Section: Targeting Of Mutant Dmpk Transcripts D Furling Et Almentioning
confidence: 53%
See 1 more Smart Citation
“…The strong reduction of the mutated DMPK transcripts by the (CUG)13 antisense could explain the restored differentiation of the infected DM1 myoblasts. This possibility is also supported by the recent report of Timchenko et al 33 showing that alterations in the activity of the CUGBP1 by the mutant DMPK transcripts causes disruption of p21-dependent control of cell cycle arrest, rendering DM1 myoblasts incapable of withdrawing from the cell cycle and fuse to form myotubes. We demonstrated that the misregulation of the CUG-binding protein in DM1 myoblasts was corrected in the antisense-infected DM1 myoblasts, indicating that molecular alterations induced by the mutated DMPK transcript were reversed by the expression of the (CUG) 13 antisense in DM1 cells.…”
Section: Targeting Of Mutant Dmpk Transcripts D Furling Et Almentioning
confidence: 53%
“…Proteins from normal, DM1 and DM1 myoblasts infected with recombinant retrovirus expressing antisense CUG repeats were incubated with radioactive RNA for 30 min at room temperature, and then subjected to UV treatment for 5 min as described. 33 The samples were treated with RNase A and then baded on 10% polyacrylamide gel containing 0.1% SDS. After electrophoresis, proteins were transferred onto nitrocellulose membrane, and subjected to radioautography.…”
Section: Uv-crosslinking Analysismentioning
confidence: 99%
“…Therefore, it seems that proliferation and differentiation are intrinsic features of the individual samples, and are not correlated with their disease status. In this respect, the HIBM primary myoblast cultures differ from those derived from myotonic dystrophy and HD patients, 18 that showed lower differentiation index than controls, and from congenital myotonic dystrophy (CMD), 19 and Duchenne muscular dystrophy (DMD) cells, 20,21 in which both proliferation and differentiation abilities are damaged. Thus, in these pathologies, basic biological functions of muscle satellite cells in culture are impaired.…”
Section: Discussionmentioning
confidence: 99%
“…16 The most commonly accepted theory is that (CTG) n expansion could affect differentiation of DM myoblasts by interfering with the signals leading to the withdrawal of cell cycle and the shift toward the differentiation program. 26,32,33 However, it should be noted that the majority of the data on in vitro differentiation of DM muscle cells derive from studies on DM1 fibroblasts converted into skeletal muscle, 18,19 from primary muscle cell cultures obtained from cDM1 fetuses 31 or from mouse muscle cells. 14,15,17,33,34 No studies focusing on muscle differentiation of human primary DM1 myoblasts cultures obtained from adult muscle DM1 biopsies are available, underlining the need to work with a model as close as possible to human regenerating skeletal muscle.…”
mentioning
confidence: 99%
“…18,19 Use of human DM1 primary myoblasts cultures has been rare, owing to limited availability, and has resulted in contradictory findings. [20][21][22][23][24][25][26][27][28][29][30][31] Various experimental models have been used to speculate about the possible effects of the DM1 mutation on the myogenic process and thus find explanation for the severe skeletal muscle immaturity and wasting of DM muscle. 16 The most commonly accepted theory is that (CTG) n expansion could affect differentiation of DM myoblasts by interfering with the signals leading to the withdrawal of cell cycle and the shift toward the differentiation program.…”
mentioning
confidence: 99%